Steam generators : description and design - Annaratone, Donatello. (Springer, 2017)
Generator Classification -- Water-Tube Generators -- Components of Water-Tube Generators -- Smoke-Tube Boilers -- Diathermic Fluid Boilers -- Fuels -- Combustion -- Heat Transfer -- Generator Efficiency -- Fluid Dynamics -- Optimization Criteria -- Computation Examples.